The Effectiveness of Coleus Amboinicus l. Leaves Extract Solution for Grade II Laceration of the Perineal Tears in Postpartum Mothers - Sulastry Pakpahan; Elly Sianturi (Science Midwifery, 2022)
Vaginal laceration (perineal tears) is one of the risks that often occurs in the process of vaginal delivery, because of the intense stretching and pressure in the birth canal when the mother pushes to deliver her baby, causing tears in the skin and muscle tissue around the birth canal. Treating birth perineal laceration is very important to accelerate healing and prevent infection of the birth canal and bladder in postpartum mothers. The leaves have a composition that can be used as an antimicrobial and antiseptic. This study aims to determine the effectiveness of a solution of extracts of the leaves of Coleus amboinicus on pain and healing of perineal lacerations in postpartum mothers. This type of quantitative research with experimental design. The research sample of postpartum mothers met the inclusion criteria, pain observation using the UPAT scale and wound healing using the REEDA scale, data analysis with the WMean Score. The results showed that postpartum pain decreased on the 5th day with an average of 1.97 (mild pain), and the healing time of perineal lacerations occurred on the 5th day, with a mean of 2.90 (good). Wax leaf extract solution is effective in reducing pain and healing time for second-degree perineal lacerations in postpartum mothers